2018
DOI: 10.1049/iet-map.2017.0553
|View full text |Cite
|
Sign up to set email alerts
|

Measurement‐based analysis of specular and dense multipath components at 94 GHz in an indoor environment

Abstract: Abstract-In this paper, we present a measurement-based analysis of the indoor radio channel characteristics of both the specular and dense multipath components (SMC and DMC) at 94 GHz within a 3 GHz bandwidth. Based on an investigation of the frequency-stationarity of this band, we have selected multiple sub-bands to perform our evaluation. A method is developed that allowed for the estimation of the specular propagation paths, after which the remainder is regarded as the diffuse spectrum. Radio channel charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This causes a pulse to spread in time. Therefore, we will investigate the PDP [33,34] and PAP [35,36]. Apart from modelling the MPCs, we will model the signal attenuation, i.e.…”
Section: Channel Soundermentioning
confidence: 99%
“…This causes a pulse to spread in time. Therefore, we will investigate the PDP [33,34] and PAP [35,36]. Apart from modelling the MPCs, we will model the signal attenuation, i.e.…”
Section: Channel Soundermentioning
confidence: 99%
“…The frequency-dependent model of the average absorption coefficient α(f ) can be easily determined from (7) and (13) and is shown in Fig. 3 (b) along with the experimental values.…”
Section: B Average Absorption Coefficientmentioning
confidence: 99%
“…It showed that the RT decreases for increasing frequency and validated the model by measurement and by comparison to reported results in the literature. Other work [13] suggested that the indoor scenario ceases to reverberate and the room electromagnetic theory is not applicable anymore at frequencies as high as 94 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…A very few short-range multipath channel measurements have also been reported for above-83 GHz frequencies, including those by Hanssens et al [9] analyzing specular and diffusive multipath propagation mechanisms at 94 GHz and reporting dominance of specular mechanism and hence small delay spread up to 15 ns. Similar level of delay spread was reported by Pometcu and D'Errico [10] for transmit-receive (Tx-Rx) distances up to 11 m, according to their indoor measurements covering 126-156 GHz frequencies.…”
Section: Introductionmentioning
confidence: 99%